Bacillus subtilis functional genomics: genome-wide analysis of the DegS-DegU regulon by transcriptomics and proteomics - Mäder, U.; Antelmann, H.; Buder, T.; Dahl, M.; Hecker, M.; Homuth, G. (Molecular genetics and genomics : MGG, 2002)
The DegS-DegU two-component regulatory system of Bacillus subtilis controls various processes that characterize the transition from the exponential to the stationary growth phase, including the induction of extracellular degradative enzymes, expression of late competence genes and down-regulation of the sigma(D) regulon. The degU32(Hy) mutation stabilizes the phosphorylated form of DegU (DegU-P), resulting in overproduction of several extracellular degradative enzymes. In this study, the pleiotropic DegS-DegU regulon was characterized by combining proteomic and transcriptomic approaches. A comparative analysis of wild-type B. subtilis and the degU32(Hy) mutant grown in complex medium was performed during the exponential and in the stationary growth phase. Besides genes already known to be under the control of DegU-P, novel putative members of this regulon were identified. Although the degU32(Hy) mutant is assumed to contain high levels of phosphorylated DegU in the exponential as well as in the stationary growth phase, many genes known to be positively regulated by DegU-P did not show enhanced expression in the mutant strain during exponential growth. This is consistent with the fact that most genes belonging to the DegS-DegU regulon are subject to multiple regulation; this is also reflected in the strong stationary-phase induction of these genes in the mutant strain. As expected, during the exponential growth phase, the sigma(D) regulon was expressed at significantly lower levels in the degU32(Hy) mutant than in the wild type.